2017
DOI: 10.1016/j.acra.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Applying Quantitative CT Image Feature Analysis to Predict Response of Ovarian Cancer Patients to Chemotherapy

Abstract: Objective This study aimed to investigate the role of applying quantitative image features computed from CT images for early prediction of tumor response to chemotherapy in the clinical trials for treating ovarian cancer patients. Materials and Methods A dataset involving 91 patients was retrospectively assembled. Each patient had two sets of pre- and post-therapy CT images. A computer-aided detection scheme was applied to segment metastatic tumors previously tracked by radiologists on CT images and computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…However, in the early stage, using the image marker computed from both prior and post-treatment ultrasound images can yield substantially higher prediction accuracy as compared to using the prior treatment images only (i.e., correlation coefficients of 0.375 vs. 0.679 as shown in Tables 3 and 5). This observation is consistent with our previous study of developing quantitative image markers computed from prior and post-chemotherapy CT images to predict the response of ovarian cancer patients to chemotherapy in the clinical trials 16 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, in the early stage, using the image marker computed from both prior and post-treatment ultrasound images can yield substantially higher prediction accuracy as compared to using the prior treatment images only (i.e., correlation coefficients of 0.375 vs. 0.679 as shown in Tables 3 and 5). This observation is consistent with our previous study of developing quantitative image markers computed from prior and post-chemotherapy CT images to predict the response of ovarian cancer patients to chemotherapy in the clinical trials 16 .…”
Section: Discussionsupporting
confidence: 92%
“…In cancer research, many previous studies have reported to develop and apply either molecular biomarkers (i.e., 2123 ) or quantitative image markers (i.e. 15,16,2426 ) to predict tumor response to chemotherapies and/or other therapeutic methods at an early stage. In this study, we investigated and demonstrated the feasibility of identifying new quantitative image markers computed from ultrasound images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They showed that MRI-derived radiomic features can discriminate between benign and malignant ovarian masses, with a high accuracy of 87% [12]. Furthermore, CT radiomic features of patients with ovarian cancer correlate with response to therapy [13], progression-free survival [14,15], and overall survival [15], and can identify patients at higher risk for recurrence [16]. Recent work by our group focused on evaluating the possible associations between CT imaging traits and texture metrics with genomics data and patient outcome [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics, in which voxel relationships are evaluated to identify textural patterns, has shown promise in separating patients into low‐ and high‐risk groups for assessment of survival . This separation of patients demonstrates the ability of radiomics features to identify small textural differences on CT images.…”
Section: Introductionmentioning
confidence: 93%